Autophagy takes it all – autophagy inducers target immune aging - Zinecker, H; Simon, AK (Company of Biologists, 2022)
Autophagy, as the key nutrient recycling pathway, enables eukaryotic cells to adapt to surging cellular stress during aging and, thereby, delays age-associated deterioration. Autophagic flux declines with age and, in turn, decreases in autophagy contribute to the aging process itself and promote senescence. Here, we outline how autophagy regulates immune aging and discuss autophagy-inducing interventions that target senescent immune cells, which are major drivers of systemic aging. We examine how cutting-edge technologies, such as single-cell omics methods hold the promise to capture the complexity of molecular and cellular phenotypes associated with aging, driving the development of suitable putative biomarkers and clinical bioassays. Finally, we debate the urgency to initiate large-scale human clinical trials. We give special preference to small molecule probes and to dietary interventions that can extend healthy lifespan and are affordable for most of the world's population.